The Impact of Brainstorming Strategies towards Students’ Writing Skill - Nilma Taula'bi' (Teaching English as a Foreign Language Overseas Journal, 2016)
This research aims are to find out the impact of brainstorming strategies towards writing skillfor the third semester students at English Education Study Program of FKIP UKI Toraja. Thisresearch employed quantitative research to find out the impact of brainstorming strategiestoward writing skill for the third semester students at English Education Study Program ofFKIP UKI Toraja Academic Year 2015/2016. The sources of the data taken from the thirdsemester students at English Education Study Program of FKIP UKI Toraja Academic Year2015/2016. The students who are selected as the subject of this research consist of 15students of class D. The instruments of the research in collecting data was written test. Theobtained data was analyzed based on generic structure of descriptive text criteria(identification, description and conclusion), then classified the students score (pre-test andpost-test) and the last used T-Test to test the hypothesis. The result of pre-test shows that 4students (26,67%) got good score, 4 students (26,67%) got fair score, 6 students (40%) gotpoor score and 1 student got very poor score. The result of post-test shows that 3 students(20%) got very good score, 10 students (66,67%) got good score, 2 students (13,33 %) gotfair score. Based on T-Test shows that to highest than t- table (5,631 > 1,785) so H0 isrefusing and H1 is accepting. It means that the brainstorming strategies have impact towardwriting skills for the third semester students of English Education Study Program of FKIPUKI Toraja Academic Year 2015/2016.